2021
DOI: 10.1212/wnl.0000000000011355
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Unconsciousness Following Severe COVID-19

Abstract: Objective:We report a case series of patients with prolonged but reversible unconsciousness following COVID-19 related severe respiratory failure.Methods:A case series of patients who were admitted to the ICU due to COVID-19 related acute respiratory failure is described.Results:After cessation of sedatives the described cases all showed a prolonged comatose state. Diagnostic neurological work-up did not show signs of devastating brain injury. The clinical pattern of awakening started with early eye opening wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…Notably, all patients who survived severe COVID-19 recovered consciousness. This observation corroborates prior reports that consciousness recovery from COVID-DoC is possible, [9][10][11] and indicates that such recovery is highly likely. Moreover, enrolling patients prospectively, soon after patients developed an unexplained DoC, revealed that the weeks-or months-long DoC described in previous reports is not common in COVID-DoC, with 50% of patients regaining consciousness within a week after continuous sedation was discontinued.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, all patients who survived severe COVID-19 recovered consciousness. This observation corroborates prior reports that consciousness recovery from COVID-DoC is possible, [9][10][11] and indicates that such recovery is highly likely. Moreover, enrolling patients prospectively, soon after patients developed an unexplained DoC, revealed that the weeks-or months-long DoC described in previous reports is not common in COVID-DoC, with 50% of patients regaining consciousness within a week after continuous sedation was discontinued.…”
Section: Discussionsupporting
confidence: 92%
“…Knowledge about DoC has advanced in the past decade [ 1 , 2 ], and data increasingly suggest that early neurorehabilitation improves outcomes [ 3 , 4 ]. Some patients with severe COVID-19 have impaired arousal and/or awareness after discontinuation of sedation [ 5 , 6 ], consistent with DoC, which may contribute to the prolonged mechanical ventilation times [ 7 ] and ICU stays [ 8 ] that are characteristic of COVID-19 critical illness. There are calls for increased early neurorehabilitation efforts in this population [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a high exposure to sedatives, mainly benzodiazepines has been independently associated with higher rates of delirium [ 7 ]. After cessation of sedatives, patients with severe respiratory failure secondary to COVID-19 may have a prolonged period of unconsciousness which may be weeks before complete recovery [ 8 ]. Caution is therefore advised when prognosticating in these patients.…”
mentioning
confidence: 99%